Unbiased analysis of obesity related, fat depot specific changes of adipocyte volumes and numbers using light sheet fluorescence microscopy. - Natalie Theobalt; Isabel Hofmann; Sonja Fiedler; Simone Renner; Georg Dhom; Annette Feuchtinger; Axel Walch; Martin Hrabĕ de Angelis; Eckhard Wolf; Rüdiger Wanke; Andreas Blutke (PLoS ONE)
In translational obesity research, objective assessment of adipocyte sizes and numbers is essential to characterize histomorphological alterations linked to obesity, and to evaluate the efficacies of experimental medicinal or dietetic interventions. Design-based quantitative stereological techniques based on the analysis of 2D-histological sections provide unbiased estimates of relevant 3D-parameters of adipocyte morphology, but often involve complex and time-consuming tissue processing and analysis steps. Here we report the application of direct 3D light sheet fluorescence microscopy (LSFM) for effective and accurate analysis of adipocyte volumes and numbers in optically cleared adipose tissue samples from a porcine model of diet-induced obesity (DIO). Subcutaneous and visceral adipose tissue samples from DIO-minipigs and lean controls were systematically randomly sampled, optically cleared with 3DISCO (3-dimensional imaging of solvent cleared organs), stained with eosin, and subjected to LSFM for detection of adipocyte cell membrane autofluorescence. Individual adipocytes were unbiasedly sampled in digital 3D reconstructions of the adipose tissue samples, and their individual cell volumes were directly measured by automated digital image analysis. Adipocyte numbers and mean volumes obtained by LSFM analysis did not significantly differ from the corresponding values obtained by unbiased quantitative stereological analysis techniques performed on the same samples, thus proving the applicability of LSFM for efficient analysis of relevant morphological adipocyte parameters. The results of the present study demonstrate an adipose tissue depot specific plasticity of adipocyte growth responses to nutrient oversupply. This was characterized by an exclusively hypertrophic growth of visceral adipocytes, whereas adipocytes in subcutaneous fat tissue depots also displayed a marked (hyperplastic) increase in cell number. LSFM allows for accurate and efficient determination of relevant quantitative morphological adipocyte parameters. The applied stereological methods and LSFM protocols are described in detail and can serve as a guideline for unbiased quantitative morphological analyses of adipocytes in other studies and species.